Validating the Children’s Sleep Habits Questionnaire Against Polysomnography and Actigraphy in School-Aged Children - Markovich, Adria Nora; Gendron, Melissa Anne; Corkum, Penny Violet (Frontiers in Psychiatry, 2015)
Sleep is a vital physiological behavior in children’s development, and as such it is important to be able to efficiently and accurately assess whether children display difficulties with sleep quality and quantity. The Children’s Sleep Habits Questionnaire [CSHQ; (1)] is one of the most commonly used assessment tools for pediatric sleep. However, this instrument has never been validated against the gold standard of sleep measurement [i.e., polysomnography (PSG)], and studies comparing it to actigraphy are limited. Therefore, the current study assessed the validity of four subscales of the CSHQ via direct comparison with PSG and actigraphy for 30 typically developing school-aged children (ages 6–12). No significant correlations between relevant CSHQ subscales and PSG variables were found. In terms of the actigraphy variables, only the CSHQ Night Wakings subscale achieved significance. In addition, sensitivity and specificity analyses revealed consistently low sensitivity and high specificity. Overall, the CSHQ Sleep Onset Delay, Sleep Duration, Night Wakings, and Sleep Disordered Breathing subscales showed low construct validity and diagnostic validity. These results underscore that caution should be taken when using the CSHQ as the sole screening tool for sleep problems in children.